Executive Functions and Emotion–Attention Interaction in Assessment of Brain Health: Reliability of Repeated Testing With Executive RT Test and Correlation With BRIEF-A Questionnaire - Erkkilä, Mikko; Peräkylä, Jari; Hartikainen, Kaisa M. (Frontiers in Psychology, 2018)
Executive functions (EF) rely on intact fronto-subcortical networks. An insult, disorder or treatment compromising brain health may impair the functioning of these widespread networks and consequently disrupt EF. Changes in brain health due to treatment or disorder can be assessed by repeating an EF test at different time points, but practice effect may confound the results. In this study we examined reliability of repeated testing using a computer-based test of EF, Executive Reaction Time (RT) Test, that allows assessment of different executive functions and emotion-attention interaction. In addition, we investigated whether performance measures correlate with scores derived from a clinically validated questionnaire of executive functions, Behavior Rating Inventory of Executive Function, Adult version (BRIEF-A). Healthy subjects performed the test twice, three to four weeks apart. When the entire tests were compared, subjects were faster and their odds to make an error reflecting disruption of working memory was lower in the second test. When two (error analysis) or four (RT analysis) blocks out of total eight test blocks were removed from the beginning of the test, the differences disappeared. In the first test emotional distractors prolonged RTs of younger, but not older, participants. In the second test emotional distractors had no effect on RTs of either age group. RTs correlated with Global Executive Composite (GEC) score of BRIEF-A. Test-retest reliability analysis showed that the Executive RT Test is reliable in repeated testing with 0.83 intraclass correlation coefficient (ICC) for RTs, 0.72 for total errors and 0.68 for working memory related errors. In summary, performance speed in the Executive RT Test correlate with subjective evaluations of executive functions and is reliable in repeated assessment when enough practice is ensured before the actual test. Thus, the Executive RT test holds promise as a potential indicator of brain health reflecting level of executive functions linked with daily life demands as well as typical emotion-attention interaction or possible aberrations in it.